Formulation of Complementary Feeding Food Using Pearl Millet and Its Sensory Evaluation (International Journal of Scientific Research in Science and Technology, 2024)
Infancy is a period of rapid development. As a result, the energy consumption per kilogram of body weight is higher than in adults. After birth, exclusive breastfeeding is recommended for at least 4-6 months. Supplemental feeding should begin after six months, when the body’s needs increase. Supplementary mixes offered on the market and given through various systems are often cereal-based. When millet is used in supplemental feeding foods, it is often ground into a fine powder to make it easier for newborns to consume. Using complementary feeding meals containing millet can help introduce your baby to new textures and flavors while also delivering the nutrients they need for healthy growth and development. However, millets have the same calorific value as grains with higher mineral content. Combining these two-three grain foods improves protein and nutritional density in later food products. Probably because of their high nutritional content, this study evaluates several studies in the literature on the utilization of these crops to generate composite food products. In the majority of underdeveloped countries, complementary foods are made from staple cereals or root crops. As a result, the current study aimed to create a supplementary mix that included pearl millet, mung beans, and pigeon peas. Sensory evaluation was conducted using composite scoring to determine the best accepted supplemental mix.